Scalable Fabrication and Integration of Graphene Microsupercapacitors through Full Inkjet Printing - Li, Jiantong; Delekta, Szymon Sollami; Zhang, Panpan; Yang, Sheng; Lohe, Martin R.; Zhuang, Xiaodong; Feng, Xinliang; Ostling, Mikael (ACS nano, 2017)
A simple full-inkjet-printing technique is developed for the scalable fabrication of graphene-based microsupercapacitors (MSCs) on various substrates. High-performance graphene inks are formulated by integrating the electrochemically exfoliated graphene with a solvent exchange technique to reliably print graphene interdigitated electrodes with tunable geometry and thickness. Along with the printed polyelectrolyte, poly(4-styrenesulfonic acid), the fully printed graphene-based MSCs attain the highest areal capacitance of ∼0.7 mF/cm2, substantially advancing the state-of-art of all-solid-state MSCs with printed graphene electrodes. The full printing solution enables scalable fabrication of MSCs and effective connection of them in parallel and/or in series at various scales. Remarkably, more than 100 devices have been connected to form large-scale MSC arrays as power banks on both silicon wafers and Kapton. Without any extra protection or encapsulation, the MSC arrays can be reliably charged up to 12 V and retain the performance even 8 months after fabrication.
CRIS-Team Scopus Importer:2023-03-20
Keywords: electrochemically exfoliated graphene; full inkjet printing; large-scale integration; microsupercapacitors; polyelectrolyte